EFFECTIVENESS OF IMPLEMENTING MARRIAGE GUIDANCE IN REDUCE THE HIGH DIVORCE RATE DURING THE COVID-19 PANDEMIC - Ririn Fauziyah; Agus Sholahudin Shidiq; Burhanatut Dyana (Fakultas Agama Islam UNISMA, 2022)
The recent COVID-19 pandemic has added to the high divorce rate. Many couples divorce because of economic factors, psychological factors, domestic violence, biology, outlook on life, and so on. The COVID-19 pandemic has changed various aspects of life, especially in family economy. The implementation of marriage guidance is considered capable of suppressing the high divorce rate during the COVID-19 pandemic, but there are also those who question its effectiveness. The descriptive method with a qualitative approach used in this study shows the fact that the implementation of marriage guidance carried out by the Office of Religious Affairs in Bojonegoro Regency has more positive impacts on prospective brides. Data collection techniques used are interviews and observation. From the results of the research that has been carried out, it can be concluded that the implementation of marriage guidance with various materials on marriage, household, reproductive and family health is quite effective in suppressing the high divorce rate during the COVID-19 pandemic. Keywords: Marriage Guidance, Divorce, Covid-19 Pandemic EFEKTIVITAS PELAKSANAAN BIMBINGAN PERKAWINAN DALAM MENEKAN TINGGINYA ANGKA PERCERAIAN DI MASA PANDEMI COVID-19 Abstrak Masa pandemi covid-19 menambah tinggi angka perceraian yang terjadi. Banyak pasangan yang memilih melakukan perceraian karena faktor ekonomi, psikologis, biologis, KDRT, perbedaan pandangan hidup, dan sebagainya. Masa pandemi covid-19 merubah berbagai sendi kehidupan terlebih dalam hal perekonomian keluarga. Pelaksanaan bimbingan perkawinan dianggap mampu menekan tingginya angka perceraian di masa pandemi, namun ada juga yang mempertanyakan keefektivannya. Penggunaan metode deskriptif dan pendekatan kualitatif dalam penelitian ini menunjukkan fakta bahwa pelaksanaan bimbingan perkawinan di Bojonegoro oleh Kantor Urusan Agama Kabupaten Bojonegoro memberikan dampak positif bagi calon pengantin. Teknik pengumpulan data dalam penelitian ini menggunakan interview dan observasi. Dari hasil penelitian diketahui bahwa pelaksanaan bimbingan perkawinan yang dilakukan dengan materi perkawinan, kerumah tanggaan, kesehatan reproduksi dan keluarga cukup efektiv dalam menekan tingginya angka perceraian pada masa pandemi covid-19. Kata kunci: Bimbingan Perkawinan, Perceraian, Pandemi Covid-19